Ideological Censorship in Lithuania, 1956–1989 - Streikus, Arūnas (Genocidas ir rezistencija, 2004)
Ideological control over public discourse was one of the essential components of the ideocratic Soviet system. Based primarily on the archival records of those Soviet state institutions which pursued ideological censorship, the article provides analysis of the methods and tendencies of the control of public life as applied in post-Stalinist Lithuania. In contrast to frequent assertions in historiography that during the post-Stalinist period ideological censorship was gradually withering, the facts provided here support the conclusion that the practice remained strong until the very collapse of the Soviet regime, except for short periods after the death of Josif Stalin and the overthrow of Nikita Khrushchev. On the other hand, the mechanism of ideological control did not manage to adjust effectively to a reality which was becoming increasingly complex over time.
Keywords: Soviet censorship; Glavlit; communist party; KGB; culture